Das Lied der Kinder
This broadcast focuses on the suffering of children in the war in Bosnia, primarily in Sarajevo, and the physical and psychological injuries caused by war. Interviews are conducted with children in various places throughout the city, including the plight of children in one of Sarajevo's orphanages. The predicament of mentally retarded children is also shown. Through a study of its youngest inhabitants, the reporters seek to dramatize the deteriorated condition of the city in the broadcast.